Editor’s Note - Sewell, Ian (Current Musicology, 2018)
This is the first issue of Current Musicology to exhibit what I hope will become a standard feature of the journal. The first article of this issue is a literature review, addressing itself to a topic of current interest in music studies. The goal is to include such a literature review as the lead article of each issue of the journal, in time creating an archive of diverse surveys that scholars can turn to in order to be brought up to date on a particular topic. Issue 103’s, written by Russell Millard, is titled “Telling Tales: A Survey of Narratological Approaches to Music”; it takes on the topic of musical narratology as discussed by scholars from the 1980s to the present. Millard’s review includes scholarship both on the established classical canon of Western art music, where the current notion of musical narratology first took hold, as well on popular music, film music, and music in video games. I hope that Millard’s contribution to the journal will be the first of many and that, as the archive grows, our lit reviews will help Current Musicology continue to be a hub for its namesake.